Voltage-Gated Calcium Channels - Catterall, William A. (Cold Spring Harbor Laboratory Press, 2011)
Voltage-gated calcium (Ca(2+)) channels are key transducers of membrane potential changes into intracellular Ca(2+) transients that initiate many physiological events. There are ten members of the voltage-gated Ca(2+) channel family in mammals, and they serve distinct roles in cellular signal transduction. The Ca(V)1 subfamily initiates contraction, secretion, regulation of gene expression, integration of synaptic input in neurons, and synaptic transmission at ribbon synapses in specialized sensory cells. The Ca(V)2 subfamily is primarily responsible for initiation of synaptic transmission at fast synapses. The Ca(V)3 subfamily is important for repetitive firing of action potentials in rhythmically firing cells such as cardiac myocytes and thalamic neurons. This article presents the molecular relationships and physiological functions of these Ca(2+) channel proteins and provides information on their molecular, genetic, physiological, and pharmacological properties.